The Diagnostic Revolution: Comparing AI Radiology and Traditional Human-Centric Practice - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The field of medical imaging is undergoing a profound transformation driven by the rapid integration of Artificial Intelligence AI. This technological shift ...
Keywords: Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning; Medical Ethics